(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Shahberi village is situated in Greater Noida and covers an area of approximately 150 acres. Being close to NH-24, ABES Engineering College, Railway Station, Fortis Hospital, Noida City Centre Metro Station and close proximity with Delhi, Ghaziabad and Noida, the place is attracted by the lower middle class families who moved to urban centres for location benefits. Most of them are lured because of relatively low rates of residential accommodation being offered by unscrupulous builders. The village has more than 200 building apartments and many more under construction without any approved plans.